Development of gamification-based e-module on global warming material for grade X - Novita Resti; Kusnadi Kusnadi; Amprasto Amprasto (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Although electronic modules offer interactivity, the integration of gamification remains limited, particularly for topics such as global warming in high school biology. This gap highlights the need for teaching materials that align with the demands of the digital era and the characteristics of modern learners. This study aims to develop a gamification-based e-module on global warming, determine the feasibility of the developed e-module, and assess student responses. This research is of the Research and Development (R&D) type using the 4D model, limited to the development stage. The instruments used in this study include interview sheets and environmental literacy questions in the define stage, the e-module design blueprint in the design stage, content feasibility validation sheets, graphic design and language validation sheets, as well as student response questionnaires in the development stage. The results of this research are as follows: (1) the feasibility of the gamification-based e-module in terms of content has a score of 85.49, categorized as